Properties of Silicon Germanium and SiGe Carbide. - Kasper, Erich; Lyutovich, Klara (Institution of Engineering & Technology Books International, Inc. [distributor], 2000)
Annotation The industrial relevance of SiGe has increased dramatically in the last few years with the manufacture of heterojunction bipolar circuits for the commercial wireless and datacomms markets by IBM and TEMIC. Major high technology companies see the development and use of SiGe as an important part of their strategy, so that there is a strong impetus to improve its characterization and exploitation. This liberally illustrated and fully indexed volume distills in a homogeneous, structured way the expertise of some 40 invited authors to comprehensively review the whole range of properties as well as SiGe; C, self-assembled nanostructures, quantum effects and device trends.
Keywords: elektronické knihy; electronic books